THE APPLICATION OF PROBLEM-BASED LEARNING MODEL BASED ON MADURA’S LOCAL WISDOM TO IMPROVE STUDENTS HOTS IN PHYSICS SUBJECT - , MAHMUD; ARIFIN IMAM SUPARDI, ZAINUL (Inovasi Pendidikan Fisika, 2019)
This study aims to describe the implementation of learning and results from HOTS improvement of students after the PBL learning model based on Maduras local wisdom was applied to Physics subjects. Design of this study using pre-experimental with one group Pre-test-posted. The subject of this study there is three classes with one experimental class and two replication classes. The implementation of learning is analyzed from the learning implementation sheet. HOTS enhancement of students is known from the results of the pre-test and post-test analyzed using t-test parametric statistics in pairs, and proceed with calculating the normalized gain value to find out the improve in HOTS learners. The results of the study showed that learning was carried out very well and there is a significant improve in HOTS of students after the PBL learning model based on Madura local wisdom was applied . HOTS improve in students is in the high category with an average the score gain is 0.804. Keywords: Problem Based Learning (PBL), Madura?s local wisdom, Higher Order Thinking Skills (HOTS)